TNFα-induced GM-CSF release from human airway smooth muscle cells depends on activation of an ET-1 autoregulatory positive feedback mechanism. Issue 12 (22nd October 2009) - Knobloch, J; Peters, H; Jungck, D; Müller, K; Strauch, J; Koch, A
Abstract : Background: There is an urgent need to inhibit endothelin-1 (ET-1) induced chronic inflammatory processes in early stages of lung diseases in order to prevent untreatable irreversible stages often accompanied by lung fibrosis and pulmonary hypertension. Nothing is known about the airway inflammation-inducing and/or maintaining role of ET-1 in human airway smooth muscle cells (HASMCs). Objective: ET-1 and granulocyte–macrophage colony-stimulating factor (GM-CSF) expression in response to tumour necrosis factor α (TNFα) and ET-1 stimulation was investigated, and the impact of mitogen-activated protein kinase (MAPK) pathways in this context was studied. To elucidate the anti-inflammatory properties of the dual endothelin receptor antagonist bosentan that targets both endothelin receptor subtypes A (ETA R) and B (ETB R), its effect on the TNFα/ET-1/GM-CSF network was investigated. Methods: ET-1 and GM-CSF expression and activation of MAPKs were investigated via quantitative reverse transcription-PCR (RT-PCR), western blotting and ELISA. Main results: Both TNFα and ET-1 activated p38 MAPK and extracellular signal-regulated kinase (ERK)-1/-2 signalling. ET-1 expression was induced by TNFα and by ET-1 itself. Both effects were inhibited by bosentan and by specific ETA R or p38 MAPK blockade. ET-1- and TNFα-induced GM-CSF expression were both reduced by bosentan as well as by specific inhibition of either ETA R, ETB R, p38 MAPK or ERK-1/-2. Conclusion: TNFα activates an ETA R- and p38 MAPK -dependent ET-1 autoregulatory positive feedback loop to maintain GM-CSF release from HASMCs. Since bosentan impairs ET-1 autoregulation and TNFα-induced ET-1 release, as well as TNFα- and ET-1-induced GM-CSF release, the present data suggest therapeutic utility for bosentan in treating particularly the early stages of chronic inflammatory airway diseases.